Therapeutics and Clinical Risk Management - 20th Anniversary - Walsh GM; Wang DY (Therapeutics and Clinical Risk Management)
Garry M Walsh,1 De Yun Wang2 1Institute of Medical Sciences, University of Aberdeen, Foresterhill, Aberdeen, AB25 2ZD, UK; 2Department of Otolaryngology, Yong Loo Lin School of Medicine, NUHS Tower Block, National University of Singapore, SingaporeCorrespondence: Garry M Walsh, Email g.m.walsh@abdn.ac.uk